X-Ray Analysis of Cadmium Oxide Nanostructured Films Synthesized with Different Precursor Molarities by Silar Method - Sarma, Hiten; Chakrabortty, Dhruba; Sarma, K.C. (Asian Journal of Chemistry, 2017)
Nanostructured cadmium oxide thin films have been synthesized onto suitably cleaned glass substrates by SILAR (successive ionic layer adsorption and reaction) method. X-ray diffraction study confirms the formation of nanocrystalline cubic phase of cadmium oxide in the films. Lattice constant is determined using Nelson Riley plots. Using X-ray broadening, crystallite sizes, lattice strain, stress and energy density were studied by using Williamson-Hall method and modified Williamson-Hall method. From literature review, it is seen that a number of researchers have applied these two methods for structural characterization of thin films of different nanocrystals, but till now modified Williamson-Hall method has not been used for CdO nanocrystals. Hence, we have used these methods for structural characterization of deposited CdO thin films. The ultra-high resolution transmission electron microscopic (UHRTEM) study shows that the shape of the particles is nearly spherical and the average particle size agrees well with the result obtained from X-ray diffraction study. Selected area electron diffraction patterns have also supported the formation of cubic phase of cadmium oxide.